2011
DOI: 10.1007/s12311-011-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Paper: Roles of the Cerebellum in Motor Control—The Diversity of Ideas on Cerebellar Involvement in Movement

Abstract: Considerable progress has been made in developing models of cerebellar function in sensorimotor control, as well as in identifying key problems that are the focus of current investigation. In this consensus paper, we discuss the literature on the role of the cerebellar circuitry in motor control, bringing together a range of different viewpoints. The following topics are covered: oculomotor control, classical conditioning (evidence in animals and in humans), cerebellar control of motor speech, control of grip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
564
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 746 publications
(596 citation statements)
references
References 301 publications
(338 reference statements)
25
564
1
6
Order By: Relevance
“…Structural plasticity in the cerebellum Recent functional imaging studies have substantiated the role of the cerebellum in motor control, automation and learning, in particular in the domain of motor skill acquisition. 51 In this study, we observed bilateral structural changes in lobules IV, V and VI. Anatomically, the cerebellar motor cortex spans the hemispheres of the lobules V, VI and VIII.…”
Section: Discussionsupporting
confidence: 50%
“…Structural plasticity in the cerebellum Recent functional imaging studies have substantiated the role of the cerebellum in motor control, automation and learning, in particular in the domain of motor skill acquisition. 51 In this study, we observed bilateral structural changes in lobules IV, V and VI. Anatomically, the cerebellar motor cortex spans the hemispheres of the lobules V, VI and VIII.…”
Section: Discussionsupporting
confidence: 50%
“…Lobule VII is again subdivided into Crus I, Crus II and lobule VIIB. Lobules I-V in the anterior lobe and lobule VIII in the posterior lobe are involved in sensorimotor tasks (Manto et al, 2012;Schmahmann, 2009, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining posture, originating and coordinating voluntary movement are some of the functionalities of the cerebellum. The cerebellum is also a direct recipient of sensory input due to the representation of the somatosensory cortex in the cerebellar cortex (Manto et al., 2012). This leads to the hypothesis that cerebellar mechanisms could explain the impaired cervical sensorimotor control.…”
Section: Discussionmentioning
confidence: 99%